Keterampilan Regulasi Emosi pada Anak di Komunitas Harapan Semarang dengan Permainan Ular Tangga - Siti Hikmah; Afifah Rahmania; Karyati Nurhaliza; Sri Puji Lestari; Adinda Ratu Kencana Asri (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to explore the emotional regulation skills of children in Harapan Community Semarang through the snakes and ladders game intervention. The method used is a participatory approach that involves children in fun game activities, so that they can learn to manage emotions in a more adaptive way. The results showed that children who previously showed maladaptive and aggressive behavior began to understand the importance of emotional regulation, such as holding back when angry and seeking help from adults. The snakes and ladders game activity not only created a relaxed atmosphere, but also provided space for children to learn cooperatively and build positive relationships with peers. Although this intervention was successful, there were some limitations, such as the constraints of setting children in a crowded environment and the short implementation time. This study concludes that a game-based approach can be an effective tool in improving children's emotional intelligence, especially in communities with limited resources, and emphasizes the need for ongoing support from parents to strengthen emotional regulation at home.